The protective role of curcumin in mitigating drug-induced toxicity in male reproductive system - Tarlan, Mitra; Moradi, Shabnam; Heidarizade, Niloofar; Tavallaei, Omid; Khazayel, Saeed; Farzaei, Mohamad Hosein; Echeverría, Javier (Frontiers in Pharmacology, 2025)
BackgroundCurcumin, a key bioactive component of turmeric (Curcuma longa L. [Zingiberaceae]), has gained considerable attention for its potential to mitigate drug-induced toxicity. This review synthesizes and clarifies current findings on curcumin’s ability to prevent the adverse effects of various pharmaceuticals.MethodsA comprehensive search using multiple databases—PubMed®, Scopus®, ScienceDirect®, and Web of Science®—was conducted for articles published up to October 2023. The current review is limited to randomized controlled trials, observational studies, and animal studies investigating the protective role of curcumin against drug-induced toxicity. The data extraction process included a variety of study characteristics, types of drugs used, curcumin dosing regimens, and reported outcomes associated with drug-induced toxicity.ResultsA total of twenty-five studies were reviewed for this analysis. Curcumin may help reduce the side effects of certain medications, including sertraline, diclofenac, paclitaxel, irinotecan, and methotrexate.DiscussionResearch also indicates that curcumin possesses antioxidant properties, reduces inflammation, and aids sperm production. Most importantly, sperm motility, density, and morphology significantly improved in curcumin-treated groups compared to the control groups undergoing toxic pharmaceutical treatment. The dosage of curcumin used in these studies ranges from 50 to 200 mg/kg body weight.ConclusionThe available evidence suggests that curcumin may serve as a protective agent for male reproductive health against drug-induced damage, based on its diverse effects in mitigating oxidative stress and inflammation, which provide potential use in preserving reproductive health in males during pharmacological interventions. However, standardization of methodologies, along with more clinical evidence, is highly required before the practical application of findings related to treatment benefits can be made. Subsequent studies should focus on optimizing the use of this compound in combination with other pharmacological agents to enhance the protective effects of curcumin on male reproductive health.